2004
DOI: 10.1093/annonc/mdh472
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of a murine antibody to MUC1 in patients with metastatic cancer: evidence for the activation of humoral and cellular antitumor immunity

Abstract: The injection of a murine antibody to MUC1 induces MUC1-specific immune responses in advanced cancer patients. Anti-MUC1 antibody increases correlated with decrease or stabilization of CA15.3 levels (P=0.03). The 2-mg dose of mAb-AR20.5 showed strongest biological activity, and will be evaluated in future efficacy trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 26 publications
2
45
0
Order By: Relevance
“…Tumor-associated MUC1 has been extensively studied as a tumor marker and as a target in cancer therapeutics (28)(29)(30)(31)(32)(33). In an attempt to target MUC1, a variety of anti-MUC1 antibodies have been generated, almost all of which react with epitopes contained within the highly immunogenic tandem 20-amino acid repeat sequence of the MUC1 a chain.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated MUC1 has been extensively studied as a tumor marker and as a target in cancer therapeutics (28)(29)(30)(31)(32)(33). In an attempt to target MUC1, a variety of anti-MUC1 antibodies have been generated, almost all of which react with epitopes contained within the highly immunogenic tandem 20-amino acid repeat sequence of the MUC1 a chain.…”
Section: Discussionmentioning
confidence: 99%
“…(14,31) Ragupathi et al (31) showed that MUC1 is a poor target for complementmediated lysis of tumor cells, because the sites for complement activation through antigen-antibody complexes are far (14,32) Polymorphic epithelial mucin is considered as one of the attractive tumor antigens for immunotherapy. (33) Several clinical studies using MUC1 tandem repeat domain-based immunogens (34,35) or mAbs (36,37) have been carried out. MUC1 peptide vaccination induced high titers of IgM and IgG andtibodies and, to a lesser extent, CTL responses.…”
Section: Discussionmentioning
confidence: 99%
“…3), and recent studies have investigated whether such antibodies initiate a vaccinal effect that is characterized by an antitumor cellular immune response. Examples of cytotoxic antibody-induced vaccinal effects from the clinic include patients treated with anti-MUC1 mAbs or anti-HER2/Neu mAbs, who generated MUC1-specific and HER2-specific T-cell responses, respectively (54,55). Because a single course of treatment with anti-CD20 mAb (rituximab) can result in long-lasting, durable responses, it has been hypothesized that treatment with this mAb may also induce a vaccinal effect in patients with lymphoma (56).…”
Section: Antibodies Prime Antitumor Immune Responses: the Vaccinal Efmentioning
confidence: 99%